Mitogenomic phylogeny of the Naticidae (Gastropoda: Littorinimorpha) reveals monophyly of the Polinicinae - Hongyue Liu; Yi Yang; Shao'e Sun; Lingfeng Kong; Qi Li (Zoologica Scripta, 2020)
The Naticidae is a species‐rich family of predatory marine gastropods with substantial interspecific morphological diversity. The classification of the Naticidae has been traditionally based on morphology data, but the phylogenetic relationships within the family are debated due to conflicting molecular results, especially regarding the monophyly of subfamilies Polinicinae and Naticinae. To further resolve the phylogenetic controversies within the Naticidae, we undertake a phylogenetic approach using 14 newly sequenced complete or nearly complete (only lacking a control region) mitochondrial genomes. Both the maximum likelihood and Bayesian inference analyses supported monophyly of the Polinicinae, but paraphyly of the Naticinae due to the placement of the enigmatic genus Notocochlis . The ancestral character reconstruction suggests that the operculum, a character that currently defines the two subfamilies, evolved from an ancestor with a calcareous operculum in the evolutionary history of naticids. In addition, the chronogram estimates that naticids was originated in late Triassic (about 227 million years ago), consistent with previous hypotheses. Our study highlights the importance of using complete mitochondrial genomes while reconstructing phylogenetic relationships within the Naticidae. The evolution scenario of the naticid operculum contributes new insights into the classification of Naticidae.